PENGARUH KEPERILAKUAN ORGANISASI TERHADAP KEGUNAAN SISTEM AKUNTANSI KEUANGAN DAERAH DI PEMERINTAH KOTA KEDIRI JAWA TIMUR - Novie Astuti Setianingsih (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2017)
The purpose of this study was to test the direct effect of behavioral factors such as the organization's supervisor support, clarity of purpose and training to improve the usefulness of the Regional Financial Accounting System. This study uses behavioral factors as the Organization of Independent Variables and Regional Financial Accounting System as Dependent Variables. The samples were as many as 15 government agencies in the town of Kediri using sample adjustment. Questionnaires were distributed 100 kuesioner number and returned to the author of a number of 75 questionnaire. Data already entered if using multiple linear regression. The results of data processing are superior support variable has a value of 3.438 t ₌ greater than t table is (3.438 > 2.042) with a p-value of 0.001 is accepted at significance level of 5% (p < 0.05). A positive value indicates a positive influence. This means that support supervisor affect the usefulness of financial accounting system daearah and H1 are accepted. Variable clarity of purpose has ₌ 3,047 t value is greater than t table of 2.042 which is 3.047 > 2.042 or p-value of 0.003 is accepted at significance level of 5% (p < 0.05). That is the purpose of clarity effect on the area of ​​financial accounting system usability and H2 are accepted. Training variables have the value of 1,346 t ₌ smaller than t table of 2.042 which is 1.346 < 2.042 or p-value of 0.183 was rejected at the 5% significance level (p > 0.05).